The Role of Multi Detector Computerized Tomography in Evaluation of Maxillofacial Fractures. - M. Muftah , Kamla; A. Beheh, Ali; Hewadi , Gebril; B. Elfseie, Arwi (Benghazi University Medical Journal, 2025)
Abstract Objective: The current study’s goals are to assess the effectiveness of Multi Detector Computerized Tomography (MDCT) in treating patients who have experienced maxillofacial trauma, describe demographic variations, describe the frequency and types of fractures that were subjected to CT scans in the Benghazi region of Libya, and compare the results with those of comparable studies carried out elsewhere in the world. Materials and Methods: We collected information from the radiology department of the al-Jala teaching hospital in Benghazi to conduct a descriptive, cross-sectional hospital-based study Between 2010 and 2013, 417 patients’ medical records who underwent head and face CT scans after suffering maxillofacial trauma were examined for the study (4 years). Results: The peak frequency, which occurred in the age group of 21 to 30, covered a range of ages from 2 to 85 years. The median age, measured by mean and standard deviation, was 29.9 +/- 12.2 years. There were six men for every woman. Road traffic accidents (RTAs) were the leading cause of fractures (75%), followed by assault (7.67%), and we found no association between gender and the cause of fracture (p = 0.537). While the orbital walls (61%) were the most frequently broken bone in simple maxillofacial fractures, the zygomaticomaxillary complex (ZMC), which makes up 22.2% of the midface, was the most vulnerable area in complex facial fractures. There was no connection between gender and the location of the fracture. Conclusion: Maxillofacial trauma can occasionally occur with serious cosmetic and functional repercussions. MDCT is required for the identification and classification of maxillofacial fractures and provides an accurate diagnosis for the design of treatment plans. Early surgical intervention is crucial for the successful management of these fractures.